Re-Tax (Restaurant Waste Tax): Pemberlakuan Pajak untuk Menekan Dampak Limbah Restoran Demi Terwujudnya Indonesia sebagai Poros Kelestarian Lingkungan Dunia - Juan Maulana Alfedo; Emilda Yofita; Laras Ayu Lintang Sari (CV Rewang Rencang, 2020)
Waste is a serious problem that occurs in various countries, especially in Indonesia. One of them is Restaurant Waste which can be categorized as organic waste and domestic liquid waste. Restaurant waste that is not processed properly can be one of the factors of environmental pollution. Moreover, in 2030 with the main problem is the increase in population in urban areas, changes in people's consumption patterns, the entry of restaurants that provide various fast food will be more concerning if not addressed immediately. Improper management of restaurant waste can cause problems, namely polluted air in the environment around the restaurant, disease nests, environmental pollution and blockage of waterways. Some of the data obtained from the Ministry of Agriculture in 2017 is the total amount of waste produced in Indonesia amounted to 187.2 million tons per year, while for Restaurant Waste 16.7 million tons per year or equivalent to 44.5%. From this, the author provides a solution in the form of the enactment of a waste tax (Re-Tax: Restaurant Waste Tax) to reduce the impact of Restaurant Waste for the realization of Indonesia as the axis of world environmental sustainability. The system that will be applied is to use maximum waste data as a basis for tax enforcement. With systematics in accordance with Law No. 42 of 2009, which is taken 10% of sales. The author uses juridical-normative writing methods, with a statutory and conceptual approach. In providing the solution is expected to be able to achieve the goal of overcoming environmental damage due to Restaurant Wastes that have not been processed, reducing the number of restaurant waste disposals, maintaining environmental sustainability and increasing local government revenue through tax enforcement.